Anti-Neoplastic Effects of Gallic Acid, a Major Component of Toona sinensis Leaf Extract, on Oral Squamous Carcinoma Cells - Robert H. Chiu; Yi-Chen Chia; Ranjan Rajbanshi; Colonya Calhoun (Molecules, 2010)
Extract of Toona sinensis (TS) has been reported to have various effects on cultured cell lines, including anti-proliferative activity in cancer cells. We have studied the effects of TS on various human oral squamous carcinoma cell lines (HOSCC), including UM1, UM2, SCC-4, and SCC-9. These cell lines were treated with TS leaf extract and screened for viability, apoptosis, necrosis, and apoptotic gene expression. Normal human oral keratinocytes (NHOK) served as a control for cytotoxic assays. Viability of TS-treated HOSCC was reduced, whereas that of NHOK was not affected. FACScan analysis revealed that the leaf extract induced apoptosis or a combination of apoptosis and necrosis, depending on cell type. Microarray and semi-quantitative RT-PCR analysis for apoptotic-related gene expression revealed that 3,4,5-trihydroxybenzoic acid (gallic acid, one of the major bioactive compounds purified from TS extract) up-regulated pro-apoptotic genes such TNF-α, TP53BP2, and GADD45A, and down-regulated the anti-apoptotic genes Survivin and cIAP1, resulting in cell death. This study suggests that gallic acid, the major bioactive compound present, is responsible for the anti-neoplastic effect of Toona sinensis leaf extract.